Nilai-Nilai Keluarga Dalam Al-Qur’an: Analisis Semiotik Representasi Konflik Keluarga Pada Film Ipar Adalah Maut - Jumroh, Fatimah; Sugeng Wanto (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study analyzes the representation of family conflict in the film Ipar Adalah Maut using a qualitative method with a Roland Barthes semiotic approach. The main objective is to uncover the layered meanings and ideologies built by the movie, then evaluate the narrative with family values in the Qur'an. Data were obtained through movie observation, review of Qur'anic commentaries (Ibn Kathir and al-Maraghi), and interviews with 10 respondents, consisting of unmarried and married groups, to enrich the analysis. The results of the semiotic analysis show that the movie, denotatively, presents an explicit story of infidelity that effectively evokes an emotional response. At the connotation level, the film builds a contrast between religious appearance and fragile morality, as well as connoting the in-law relationship as a hidden threat. Ultimately, the movie creates the myth that infidelity is an inevitable consequence of human weakness. However, when this myth is confronted with family values in the Qur'an, a more robust discourse emerges. The Qur'ān offers a strong foundation of marriage, namely sakinah, mawaddah and rahmah, built on moral commitment and responsibility. Respondents intuitively rejected this destructive myth and instead used the movie as a mirror to reflect on the importance of returning to Qur'anic values as practical guidance. Thus, the study concludes that while movies can serve as critical mirrors, the findings also confirm the relevance of Qur'anic values in building resilient families, challenging the myth of fragility often portrayed in popular media.